PENGARUH EXTERNALITAS PADA NET ENERGY RATIO PRODUKSI BIODIESEL MIKROALGA = Externalities Effect on Net Energy Ratio of Microalgae Biodiesel Production - Santoso, Arif Dwi; ., Kardono; Susanto, Joko P. (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2013)
In the future, Indonesia is predicted to be hit by national energy crisis so that it needs to do some efforts to overcome its dependences on these fossil energy sources. One of the efforts to lower high dependency on fossil energy sources is to find renewable energy sources. Microalgae has a great potential as a renewable energy source because it has the advantages of high productivity and sustainability. Development of microalgal biomasses as a renewable energy source is however, constrained by high cost of biomass production and low value of NER (net energy ratio) comparing tothese of other biomasses, like palm oil, jatrophaand tubers. Literature study shows that the method of NER calculation on biodiesel production does not yet include environmental variables. This researchis therefore to evaluate the values of NER before and after the addition of environmental commodity variables that consist of social, environmental and land use cost. Results of NER values calculatedusing existing LCA and modification LCA method are found to be 0,62 ± 0,078 and 0,60 ± 0,075 for algal biodiesel and 4,17 ± 0,79 and 3,22 ± 0,61 for palm biodiesel. The lower value of NER value differences for algal biomass indicates that biodiesel production from algal biomass is more environmentally-friendly. In addition, it is predicted that microalgae will have a significant contribution in the green house gases (GHGs) mitigation by replacing fossil fuel in the future through its role as a biodiesel. Keywords: net energy ratio, life cycle analysis, environmental commodity, microalgae, biodieselAbstrakDi masa depan, Indonesia diperkirakan akan dilanda krisis energi nasional sehingga perlu melakukan upaya untuk mengatasi ketergantungan terhadap energi fosil tersebut. Salah satu upayauntuk menurunkan ketergantungan pada energi fosil adalah untuk menemukan sumber energi terbarukan. Mikroalga memiliki potensi besar sebagai sumber energi terbarukan karena memiliki keuntungan dari produktivitas tinggi. Pengembangan biomasa mikroalga sebagai sumber energi terbarukan terkendala oleh tingginya biaya produksi dan nilai rendah APM (rasio energi bersih) dibandingkan dengan biomasa lainnya, seperti kelapa sawit ataupun umbi-umbian. Studi literatur menunjukkan bahwa metode perhitungan APM pada produksi biodiesel belum menyertakan variabel lingkungan. Oleh karena itu penelitian ini adalah untuk mengevaluasi nilai-nilai APM sebelum dansesudah penambahan variabel komoditas lingkungan yang terdiri dari biaya sosial, lingkungan dan penggunaan lahan. Hasil nilai NER dihitung dengan menggunakan LCA yang ada dan metode LCAmodifikasi yang ditemukan 0,62 ± 0078 dan 0,60 ± 0,075 untuk biodiesel alga dan 4,17 ± 0,79 dan 3,22 ± 0,61 untuk biodiesel sawit. Nilai yang lebih rendah dari perbedaan nilai APM untuk biomassaalga menunjukkan bahwa produksi biodiesel dari biomassa alga lebih ramah lingkungan. Selain itu, diperkirakan bahwa mikroalga akan memiliki kontribusi yang signifikan dalam mitigasi gas rumahkaca (GRK) dengan mengganti bahan bakar fosil. Kata kunci: rasio energi, analisa siklus hidup, komoditas lingkungan, mikroalga, biodiesel